Perennial Pigeonpea as a Vegetative Barrier for Protection and Production in Millet-lentil Cropping Systems - Tyagi, P. C.; Joshi, B. P.; Sharma, N. K.; Khullar, A. K. (Indian Forester, 2001)
To evolve a promising cropping system which reduced run-off, soil loss and increases total production under marginal rainfed lands of Doon Valley and lower Himalayan region, ragilentil and kodomillet-lentil systems with and without vegetative barriers were constructed and tested at 2% sloping experimental field. The treatments were monitored for run-off, soil loss and productiou parameters. It was observed that incorporation of perennial Pigeonpea hedge rows in the cropping systems reduced the run-off and soil loss but significantly increased total production and net returns.